Low-energy phenomenology of trinification: an effective left-right-symmetric model - Hetzel, Jamil; Stech, Berthold (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The trinification model is an interesting extension of the Standard Model (SM) based on the gauge group SU(3)C×SU(3)L×SU(3)R. We study its low-energy phenomenology by constructing a low-energy effective field theory, thereby reducing the number of particles and free parameters that need to be studied. The resulting model predicts that several new scalar particles have masses in the O(100 GeV) range. We study a few of the interesting phenomenological scenarios, such as the presence of a light fermiophobic scalar in addition to a SM-like Higgs, or a degenerate (twin) Higgs state at 126 GeV. We point out regions of the parameter space that lead to measurable deviations from SM predictions of the Higgs couplings. Hence, the trinification model awaits crucial tests at the Large Hadron Collider in the coming years.